Developing Android applications using agent-oriented programming - Russell, Sean; Doyle, Owen; Collier, Rem W. (ISKE : 2017 12th International Conference on Intelligent Systems and Knowledge Engineering : 24-26 November 2017, 2017)
Designing applications for current generation context aware mobile devices is a complex task. Programmers are required to have a deep knowledge of the underlying systems and APIs in order to complete an application. This paper presents a system that takes advantage of the high level of abstraction common to agent-oriented programming languages to reduce the difficulty in creating context-sensitive applications for Android devices.